The globular cluster system of NGC 1399: V. dynamics of the cluster system out to 80 kpc - Shuberth, Y. (2010)
Globular clusters (GCs) are tracers of the gravitational potential of their host galaxies. Moreover, their kinematic properties may provide clues for understanding the formation of GC systems and their host galaxies. We use the largest set of GC velocities obtained so far of any elliptical galaxy to revise and extend the previous investigations (Richtler et al. 2004) of the dynamics of NGC 1399, the central dominant galaxy of the nearby Fornax cluster of galaxies. The GC velocities are used to study the kinematics, their relation with population properties, and the dark matter halo of NGC 1399. We have obtained 477 new medium-resolution spectra (of these, 292 are spectra from 265 individual GCs, 241 of which are not in the previous data set). with the VLT FORS 2 and Gemini South GMOS multi-object spectrographs. We revise velocities for the old spectra and measure velocities for the new spectra, using the same templates to obtain an homogeneously treated data set. Our entire sample now comprises velocities for almost 700 GCs with projected galactocentric radii between 6 and 100 kpc. In addition, we use velocities of GCs at larger distances published elsewhere. Combining the kinematic data with wide-field photometric Washington data, we study the kinematics of the metal-poor and metal-rich subpopulations. We discuss in detail the velocity dispersions of subsamples and perform spherical Jeans modelling. The most important results are: the red GCs resemble the stellar field population of NGC 1399 in the region of overlap. The blue GCs behave kinematically more erratic. Both subpopulations are kinematically distinct and do not show a smooth transition. It is not possible to find a common dark halo which reproduces simultaneously the properties of both red and blue GCs. Some velocities of blue GCs are only to be explained by orbits with very large apogalactic distances, thus indicating a contamination with GCs which belong to the entire Fornax cluster rather than to NGC 1399. Also, stripped GCs from nearby elliptical galaxies, particularly NGC 1404, may contaminate the blue sample. We argue in favour of a scenario in which the majority of the blue cluster population has been accreted during the assembly of the Fornax cluster. The red cluster population shares the dynamical history of the galaxy itself. Therefore we recommend to use a dark halo based on the red GCs alone. The dark halo which fits best is marginally less massive than the halo quoted previously. The comparison with X-ray analyses is satisfactory in the inner regions, but without showing evidence for a transition from a galaxy to a cluster halo, as suggested by X-ray work.